Consumers’ Choice and Decision towards Low Cost Airline in the Upper South provinces of Thailand - Sakdaar, Pornapaktra; Poon-Ead, Jeerati (Chophayom Journal, 2018)
This article aimed to display the idea of examines the factors affecting the consumers’ choice and decision towards low-cost airlines in the Upper South provinces of Thailand. These routes are the focus of the article because of high competition and high service demands. The framework is based on synthesis of previous studies on consumer decisions toward airlines. This paper will discuss about factors influencing decision-making and their relationships to airline trends, using the Thai domestic market as an example. The secondary review will be illustrated factors to measure attitudes about pre-flight, in-flight and post-flight service and their effect on service quality perceptions and consumer behaviors in the future study.